Hubungan Antara VO2 MAX dengan Indeks Prestasi Kumulatif (IPK) Mahasiswa IKOR FIK UNIMED. - Nurman Hasibuan; Syahputra Manik; Rosmaini Hasibuan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The ability to perform daily tasks that require endurance can be considered as physical ability. The physical abilities of each individual certeinly vary from one to another. Good physical ability can be seen from good physical fitness. One of the good physical fitness of students can be seen from the level of VO2 Max owned by students. This study aims to determaine wether there is a relationship between VO2 Max and the Grade Point Average (GPA) of IKOR FIK Unimed students. This research uses survey method. The sample was 76 people who were taken using the formula according Al-Rasyid the number of total IKOR FIK Unimed students was 322 people. The data collection technique uses tests and measurements for VO2 Max data, and is taken from secondary data for student GPA data. Data analysis technique using spearmen rank. Teh results showed that there was no significant relationship between VO2 Max and the Grade Point Average (GPA) of IKOR FIK Unimed students. This means that the student’s VO2 Max level is not related to the Grade Point Average (GPA).